Educational Policy In The School Operational Assistance Program To Improve The Quality Of Education - Fathonah Nasrullah (Amandemen: Journal of Learning, Teaching and Educational Studies, 2023)
The aim of this research is to describe and analyze how education policies in the School Operational Assistance program improve the quality of education. The research instrument used was a descriptive qualitative approach, data collection was based on library research. The results of this research are that educational policies in the school operational assistance program to improve the quality of education have been running quite well, Process Which quality achieved when all organizer education (including maker policy And holder interest) involved active in maintenance education the in accordance with role And not quite enough he answered, school operational assistance is one of the most important bridges for educational institutions and the community, because the funds spent by schools to achieve quality education are very large, but with BOS funds schools will be helped so that they can run effectively, and are very important for people who experience an unstable economy but have the desire to send their children to a higher level of education, with BOS funds students can study diligently without thinking about school fees, quality education is education that is able to create students who are active, intelligent, creative and graduates who are useful for themselves and for the country.